Randomized clinical trial of BCG vaccine in patients with convalescent COVID‐19: Clinical evolution, adverse events, and humoral immune response - Jalalizadeh, Mehrsa; Buosi, Keini; Dionato, Franciele A. V.; Dal Col, Luciana S. B.; Giacomelli, Cristiane F.; Ferrari, Karen L.; Pagliarone, Ana Carolina; Leme, Patrícia A. F.; Maia, Cristiane L.; Yadollahvandmiandoab, Reza; Trinh, Quoc‐Dien; Franchini, Kleber G.; et al. (Journal of internal medicine, 2022)
Background The Bacillus Calmette–Guérin (BCG) vaccine may confer cross‐protection against viral diseases in adults. This study evaluated BCG vaccine cross‐protection in adults with convalescent coronavirus disease 2019 (COVID‐19). Method This was a multicenter, prospective, randomized, placebo‐controlled, double‐blind phase III study (ClinicalTrials.gov: NCT04369794). Setting: University Community Health Center and Municipal Outpatient Center in South America. Patients: a total of 378 adult patients with convalescent COVID‐19 were included. Intervention: single intradermal BCG vaccine (n = 183) and placebo (n = 195). Measurements: the primary outcome was clinical evolution. Other outcomes included adverse events and humoral immune responses for up to 6 months. Results A significantly higher proportion of BCG patients with anosmia and ageusia recovered at the 6‐week follow‐up visit than placebo (anosmia: 83.1% vs. 68.7% healed, p = 0.043, number needed to treat [NNT] = 6.9; ageusia: 81.2% vs. 63.4% healed, p = 0.032, NNT = 5.6). BCG also prevented the appearance of ageusia in the following weeks: seven in 113 (6.2%) BCG recipients versus 19 in 126 (15.1%) placebos, p = 0.036, NNT = 11.2. BCG did not induce any severe or systemic adverse effects. The most common and expected adverse effects were local vaccine lesions, erythema (n = 152; 86.4%), and papules (n = 111; 63.1%). Anti–severe acute respiratory syndrome coronavirus 2 humoral response measured by N protein immunoglobulin G titer and seroneutralization by interacting with the angiotensin‐converting enzyme 2 receptor suggest that the serum of BCG‐injected patients may neutralize the virus at lower specificity; however, the results were not statistically significant. Conclusion BCG vaccine is safe and offers cross‐protection against COVID‐19 with potential humoral response modulation. Limitations: No severely ill patients were included.